ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KPP PRATAMA BATAM SELATAN - Octaviani, Vira; Efriyenti, Dian (SCIENTIA JOURNAL, 2024)
Taxes provide vital services in a nation, particularly for the sustainability of the government system. Taxes are utilized as a source of money to fund agriculture, trade, industry, health care, education, and other services. The tax business is essential to meeting a country's development needs. The bigger the country's tax revenue, the greater its income.To boost people's prosperity and well-being, more compliance with tax responsibilities is required. Individuals in the KPP Pratama Batam Selatan, however, continue to be noncompliant with their tax duties. There are a variety of elements that influence tax compliance. The study's goal is to look at the influence of tax knowledge, punishments, and rates on tax compliance. Questionnaires are distributed to taxpayers as part of the data gathering process. The purposive sampling approach and the Slovin formula were employed to obtain the sample, which yielded 398 responses. The study found that tax knowledge and tax punishments have a considerable impact on tax compliance, whereas tax rates have an influence but are minor. Taxation knowledge, tax sanctions, and tax rates all have a substantial impact on tax liability.